Analisis Penerapan Media Busur Panah Pada Pembelajaran IPA Materi Gaya Pegas Untuk Meningkatkan Motivasi Belajar Murid Kelas V SD Inpres Hulu Atas - Paulus R. Esuwe; Triwiyono; Ewendi W. Mangolo; Yektiningtyas, Wigati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of bow-and-arrow media in Science learning, particularly on the topic of spring force, and to examine its impact on elementary school students’ learning motivation. The study employed a qualitative approach with a descriptive design to obtain an in-depth understanding of the process and outcomes of using this instructional media in classroom learning activities. The research participants were fifth-grade students at SD Inpres Hulu Atas. Data were collected through observation, interviews, and documentation, while data analysis was conducted using an interactive model consisting of data reduction, data presentation, and conclusion drawing. The findings revealed that the implementation of bow-and-arrow media had a positive effect on the Science learning process. The use of this concrete learning media created a more engaging, interactive, and enjoyable learning environment, encouraging students to actively participate in every stage of the lesson. Through practical activities involving the bow and arrow, students were able to directly observe the relationship between force, elasticity, and energy in springs, making the concepts easier to understand and remember. Furthermore, the bow-and-arrow media helped bridge abstract concepts with students’ real-life experiences. The improvement in students’ learning motivation was reflected in their increased attention to the learning materials, heightened curiosity, active participation in questioning and discussions, and persistence in completing learning tasks. Students also demonstrated positive attitudes toward Science learning because they found the lessons more interesting and motivating. Therefore, concrete learning media such as the bow and arrow proved effective in enhancing students’ learning motivation and understanding of spring force concepts in elementary school Science education. These findings imply that the use of innovative instructional media can serve as an effective alternative for improving the quality of Science learning at the elementary school level.